2021
DOI: 10.3390/brainsci11030377
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 10 Hz and 20 Hz tACS in Network Integration and Segregation in Chronic Stroke: A Graph Theoretical fMRI Study

Abstract: Transcranial alternating current stimulation (tACS) has emerged as a promising technique to non-invasively modulate the endogenous oscillations in the human brain. Despite its clinical potential to be applied in routine rehabilitation therapies, the underlying modulation mechanism has not been thoroughly understood, especially for patients with neurological disorders, including stroke. In this study, we aimed to investigate the frequency-specific stimulation effect of tACS in chronic stroke. Thirteen chronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Neubauer combined θ tACS with fMRI to analyze the brain changes induced by prickles (Neubauer et al, 2017 ). Chen analyzed the role of 10-Hz and 20-Hz tACS in the integration and isolation of chronic stroke networks by fMRI (Chen et al, 2021 ). These studies point out a direction for us to explore the mechanism of tACS from various angles in the future.…”
Section: Discussion and Futurementioning
confidence: 99%
“…Neubauer combined θ tACS with fMRI to analyze the brain changes induced by prickles (Neubauer et al, 2017 ). Chen analyzed the role of 10-Hz and 20-Hz tACS in the integration and isolation of chronic stroke networks by fMRI (Chen et al, 2021 ). These studies point out a direction for us to explore the mechanism of tACS from various angles in the future.…”
Section: Discussion and Futurementioning
confidence: 99%
“…Studies using tACS have already shown increases in cerebral blood flow in both hemispheres and lowered resistance in the intracranial vascular bed in patients during the acute phase to 3 months after stroke (Salinet et al, 2014;Wu et al, 2016). Patients in the chronic phase after stroke have also shown network integration and segregation in both motor-related regions and on a whole-brain level after 10 and 20 Hz tACS stimulation (Chen et al, 2021). However, as with tDCS, more research is required to determine the mechanisms underlying the effects of tACS.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%
“…In comparison to the other EEG frequencies, EEG having the same or very similar frequency to tACS showed the greatest increase in amplitude when stimulated by tACS (Ali et al, 2013 ; Schmidt et al, 2014 ). Nevertheless, there is still a gap of knowledge related to the precise mechanisms responsible for the effects of tACS on brain activity as current evidence speaking in favor of the aforementioned tACS mechanisms are rather indirect (Zaehle et al, 2010 ; Krause et al, 2019 ; Chen et al, 2021 ; Frohlich and Townsend, 2021 ).…”
Section: Mechanisms Of Tacs and Nfbmentioning
confidence: 99%
“…The effects of tACS or NFB on brain plasticity have been already investigated by using fMRI (Kluetsch et al, 2014 ; Nicholson et al, 2016 ; Abellaneda-Pérez et al, 2020 ; Gundlach et al, 2020 ; Mondino et al, 2020 ; Chen et al, 2021 ), the measurement of a motor-evoked potential (MEP) by transcranial magnetic stimulation (TMS) (Ros and Gruzelier, 2011 ; Wach et al, 2013 ; Vallence et al, 2021 ). The link between EEG changes and changes in the levels of the concentration of the molecular substrates of plasticity after tACS/NFB intervention has been already studied too Lee et al, 2019 ; Wischnewski et al, 2019 ; Markiewicz and Dobrowolska, 2020 ; Riddle et al, 2020a ).…”
Section: Mechanisms Of Tacs and Nfbmentioning
confidence: 99%